Acute necrotizing calculous cholecystitis after treatment with ceftriaxone in an elderly patient: a case report - Tsunehiko Shigemori; Ichiro Imoto; Yasuhiro Inoue; Ryo Nishiwaki; Natsuko Sugimasa; Tetsuya Hamaguchi; Midori Noji; Kenji Takeuchi; Yoshiyuki Ito; Taro Yasuma; Esteban C. Gabazza; Toshio Kato (Surgical Case Reports)
Abstract Background Ceftriaxone, a third-generation cephalosporin antibiotic with a long plasma half-life, is widely used to treat various infections. The use of ceftriaxone can sometimes induce biliary sludge or stone formation. Although most cases of ceftriaxone-induced pseudolithiasis are asymptomatic or mild and resolve with discontinuation of the drug, we experienced an elderly case of severe acute necrotizing calculous cholecystitis after administration of ceftriaxone. Case presentation A 72-year-old male patient was admitted to our hospital because of acute diverticulitis in ascending colon. Ceftriaxone was administered at a dose of 2 g/day for 6 days. Although he recovered after therapy, he was readmitted about 2 weeks later because of severe pain with rebound tenderness in the right upper quadrant. An abdominal imaging study revealed stones and sludge in the gallbladder that were not observed before starting ceftriaxone therapy. Therefore, antibiotic treatment with flomoxef 2 g/day was indicated. However, on the fifth day of readmission, the peritoneal irritation symptoms in the right upper quadrant worsened, and elevated inflammatory response and liver dysfunction were observed. Cholecystectomy was performed based on these findings. The resected inflamed gallbladder showed acute necrotizing cholecystitis with sand granular gallstones. A comparative analysis of the infrared spectroscopic pattern of the composition of gallstones collected during surgery with that of the ceftriaxone powder revealed that both have very similar infrared spectroscopic patterns. Conclusions Ceftriaxone-related pseudolithiasis is generally reversible and mainly observed in children. Here, we report a rare case of ceftriaxone-related acute necrotizing cholecystitis in an elderly patient. We confirmed that the stones in the gallbladder are composed of ceftriaxone. The older age, dehydration, fasting, and long-time bed rest during the administration of high-dose ceftriaxone were the potential risk factors for gallstone formation.